Influence of energy demand response actions on thermal comfort and energy cost in electrically heated residential houses. Issue 3 (March 2017) - Alimohammadisagvand, Behrang; Alam, Sadaf; Ali, Mubbashir; Degefa, Merkebu; Jokisalo, Juha; Sirén, Kai
This study has two aims to investigate the energy demand response (DR) actions on thermal comfort and energy cost in detached residential houses (1960, 2010 and passive) in a cold climate. The first one is to find out the acceptable range of indoor air and operative temperatures complying with the recommended thermal comfort categories in accordance with the EN 15251 standard. The second one is to minimize the energy cost of electric heating system by means of the DR control strategy, without sacrificing thermal comfort of the occupants. This research was carried out with the validated dynamic building simulation tool IDA Indoor Climate and Energy. Three different control strategies were studied: A) a strategy based on real-time hourly electricity price, B) new DR control strategy based on previous hourly electricity prices and C) new predictive DR control strategy based on future hourly electricity prices. The results show that the lowest acceptable indoor air and operative temperatures can be reduced to 19.4℃ and 19.6℃, respectively. The maximum annual saving in total energy cost is about 10% by using the control algorithm C.